A Colorimetric and Fluorescent Chemosensor for Cu2+ Detection in Aqueous Solution. Issue 12 (1st December 2016) - Li, Lian-Qing
Abstract : A novel fluorescent chemosensor, 10-(benzo[d]thiazol-2-yl)-2, 3, 6, 7-tetrahydro- 1H-pyrano[2, 3-f]pyrido[3, 2, 1-ij]quinolin-11(5H)-imine(L), was been successfully developed and well characterized. Sensor L exhibits high selectivity for Cu 2+ over other ions (Ag +, Pb 2+, Cu 2+, Ni 2+, Fe 3+, Co 2+, Zn 2+, Hg 2+, and Cd 2+ ) with colorimetric and fluorescence turn-off properties in aqueous solutions. Furthermore, the reversible recognition process was confirmed by EDTA experiment and sensor L showed practical application in detection Cu 2+ in tap water.